PhD Student Ambassadors: Partners in Promoting Graduate Research - Mitchell, Liesel; Seyedmehdi, Shabnam; Spronken-Smith, Rachel (International Journal for Students as Partners, 2017)
The aims of this research were to explore the experiences of staff and postgraduate students in an ambassador scheme, develop a model of partnering with postgraduate students in the administrative space, and consider implications for partnership initiatives. A qualitative case study was undertaken of a “Graduate Research Ambassador Scheme”, involving a dean employing two PhD students as paid ambassadors to help promote a vibrant graduate research culture. Research diaries were kept by each partner, regular research discussions occurred, and each partner wrote a reflective account of their experiences. These data were collaboratively analysed using a general inductive approach. All partners had very positive experiences, but there was some uncertainty regarding the nature of the role and some institutional challenges. A model of staff-student partnership within the administrative space was developed that included three main influences on effective partnerships: roles in partnership, structural characteristics, and personal characteristics. The model highlights the need for clear articulation of roles and tasks, the challenge of institutional cultures, and the way that resources, time, and space can either hinder or help partnerships. Personal characteristics such as trust, respect, and informal communication can significantly mitigate challenges and build fruitful partnerships.